2013
DOI: 10.1016/j.ijid.2013.01.025
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of uropathogenic virulence genes in Escherichia coli isolated from patients with urinary tract infection

Abstract: Our study showed that investigation of the bacterial pathogenicity associated with UTI may contribute to a better medical intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

29
118
5
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(159 citation statements)
references
References 16 publications
29
118
5
1
Order By: Relevance
“…Additionally, all investigated virulence genes were more prevalent in pathogenic isolates than in commensal isolates, consistent with previous studies [2,31]. The fimH gene (81.6%) was the most frequent virulence gene, particularly as it appeared in 95.8% of uropathogenic isolates, which is in accordance with a previous study that reported that the fimH gene played an important role in the initiation of colonization and infection, particularly in urinary tract infections [24,32]. papG allele I (0.6%) and papG allele II (3.4%) were rarely found compared with the papG allele III (23.6%), indicating that they have little importance in the pathogenesis of E. coli.…”
Section: Discussionsupporting
confidence: 91%
“…Additionally, all investigated virulence genes were more prevalent in pathogenic isolates than in commensal isolates, consistent with previous studies [2,31]. The fimH gene (81.6%) was the most frequent virulence gene, particularly as it appeared in 95.8% of uropathogenic isolates, which is in accordance with a previous study that reported that the fimH gene played an important role in the initiation of colonization and infection, particularly in urinary tract infections [24,32]. papG allele I (0.6%) and papG allele II (3.4%) were rarely found compared with the papG allele III (23.6%), indicating that they have little importance in the pathogenesis of E. coli.…”
Section: Discussionsupporting
confidence: 91%
“…A subset of E. coli is capable of causing enteric/diarrheal diseases and a different cluster causes extra-intestinal infections, including urinary tract infection (UTI) (1). Uropathogenic E. coli (UPEC), a gram negative bacillus, is the main etiologic agent and predominant microorganism causing UTIs (in 50-80z) (2)(3)(4). UTI is the most common bacterial infectious disease encountered in clinical practice, accounting for considerable morbidity rates and high medical costs (4).…”
Section: Introductionmentioning
confidence: 99%
“…Uropathogenic E. coli (UPEC), a gram negative bacillus, is the main etiologic agent and predominant microorganism causing UTIs (in 50-80z) (2)(3)(4). UTI is the most common bacterial infectious disease encountered in clinical practice, accounting for considerable morbidity rates and high medical costs (4). UTIs are one of the most prevalent and significant community-acquired and nosocomial infections, with 150 million cases of this extraintestinal infection occurring annually worldwide (5,6).…”
Section: Introductionmentioning
confidence: 99%
“…These results agree with published reports, which emphasize the predominance of fimbriae type 1 among the UPEC strains (Jalali et. al., 2015;Tarchouna et al, 2013;Usein et al, 2001). One important virulence factor of E. coli causing UTI is fimbriae-mediated adherence.…”
Section: Discussionmentioning
confidence: 99%